Produksi asam lemak dari dedak melalui proses hidrolisis enzimatis secara in situ - Indah Hartati; Fahmi Arifan; Mohammad Endy Yulianto (Jurnal Rekayasa Proses, 2011)
Indonesia has potential to produce fatty acid from rice bran which is abundantly available as a side product of rice field activities. Rice bran contains lipase enzyme which is a catalyst for hydrolysis of triglycerides largely found in rice bran. The present work aimed to investigate the hydrolysis process of triglyceride from rice bran by activated lipase enzyme. Effect of the presence of phosphate compounds as buffer on fatty acid production was studied. The amount of fatty acid produced during hydrolysis with the use of buffer was compared to that without buffer. The parameters studied in the present work were volume of buffer (0% to 25% of water volume), rice bran-water ratio (1:1 to 1:6 w/v) and reaction temperature (30°C – 50°C). Experimental results showed that ions in the buffer solution could increase the activity and stability of lipase enzyme. The addition of buffer was found to increase fatty acid yield up to 48%. The highest fatty acid results ware obtained at the operation condition at which buffer volume of 5%, reaction temperature of 50°C and rice bran-water ratio of 1:5 where the acid number was 2.63 mgek NaOH/g rice bran.